Modification of intracellular glutathione status does not change the cardiac trapping of (64)Cu(ATSM) - Shaughnessy, Fiona (EJNMMI Res, 2014)
BACKGROUND: The trapping mechanisms of the PET hypoxia imaging agent copper(II)-diacetyl-bis(N(4)-methylthiosemicarbazone) ((64)Cu(ATSM)) remain unresolved, although its reduction prior to dissociation may be mediated by intracellular thiols. Glutathione (GSH) is the most abundant intracellular thiol, and its redox status changes in cancer cells and ischaemic myocardium (two prime applications for (64)Cu(ATSM) PET). We therefore investigated whether modification of intracellular GSH content affects the hypoxia selectivity of (64)Cu(ATSM). METHODS: Isolated rat hearts (n = five per group) were perfused with aerobic buffer (equilibrated with 95%O(2)/5%CO(2)) for 15 min, then hypoxic buffer (95%N(2)/5%CO(2)) for 20 min. Cardiac glutathione was depleted by buthionine sulphoximine (BSO, 4 mmol/kg/ 48 h intraperitoneal), or augmented by N-acetyl cysteine (NAC, 4 mmol/L) in the perfusion buffer. Cardiac (64)Cu retention from three 2-MBq bolus injections of (64)Cu(ATSM) before and during hypoxia was then monitored by NaI detectors. RESULTS: Cardiac GSH content was elevated by NAC and depleted by BSO (from 7.9 ± 2.0 to 59.3 ± 8.3 nmol/mg and 3.7 ± 1.0 nmol/mg protein, respectively; p < 0.05). Hypoxia did not affect cardiac GSH content in any group. During normoxia, tracer washed out bi-exponentially, with 13.1% ± 1.7% injected dose being retained; this was not affected by GSH augmentation or depletion. Hypoxia significantly increased tracer retention (to 59.1% ± 6.3%, p < 0.05); this effect was not modified by GSH augmentation or depletion. CONCLUSION: Modification of GSH levels had no impact upon the pharmacokinetics or hypoxia selectivity of (64)Cu(ATSM). While thiols may yet prove essential for the intracellular trapping of (64)Cu(ATSM), they are not the determinants of its hypoxia selectivity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13550-014-0040-8) contains supplementary material, which is available to authorized users.